THE TRANSFORMING CONTEXT OF THE SOUTH AFRICAN ASSOCIATION OF ART HISTORIANS (SAAAH) - Ramgolam, Judy (My University, 2011)
„1994 has marked the start of a new political dispensation. In order to concretise the transformation process, national frameworks of reference have been instituted. The purpose of this exploratory study was to determine whether the South African Association of Art Historians (SAAAH) should be aligned with the national transformation frameworks. Over the years there have been concerns by both black and white art historians who were of the opinion that the SAAAH had not transformed in line with the national policies and had remained an elitist body. The Association was analysed in terms of its organisational structure, design and political influences. One of the main findings of the research was that the SAAAH was at a decline stage. (Robbins, 1990: 20) Some of the salient factors that contributed to the decline of the SAAAH were its inability to respond to the changing needs of the environment and the lack of understanding of the need to diversify its membership
MM thesis - P&DM
Keywords: Transformation; South African Association of Art Historians